2016
DOI: 10.1038/srep32459
|View full text |Cite
|
Sign up to set email alerts
|

Deep sexual dimorphism in adult medaka fish liver highlighted by multi-omic approach

Abstract: Sexual dimorphism describes the features that discriminate between the two sexes at various biological levels. Especially, during the reproductive phase, the liver is one of the most sexually dimorphic organs, because of different metabolic demands between the two sexes. The liver is a key organ that plays fundamental roles in various physiological processes, including digestion, energetic metabolism, xenobiotic detoxification, biosynthesis of serum proteins, and also in endocrine or immune response. The sex-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 38 publications
3
37
0
Order By: Relevance
“…Females and males clustered distinctly in unsupervised clustering by gene expression, as has been observed in other studies of fish liver at a reproductive stage (Qiao et al 2016). Interestingly, there was a large difference in the number of transcripts assigned to modules between the sexes; of the 25 k most connected transcripts, females had 76% transcripts assigning to a module, and males only 28%.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Females and males clustered distinctly in unsupervised clustering by gene expression, as has been observed in other studies of fish liver at a reproductive stage (Qiao et al 2016). Interestingly, there was a large difference in the number of transcripts assigned to modules between the sexes; of the 25 k most connected transcripts, females had 76% transcripts assigning to a module, and males only 28%.…”
Section: Discussionsupporting
confidence: 81%
“…Comparisons between the sexes are complicated by the fact that sex bias in networks can be tissue-specific, with modules more preserved between sexes in brain and muscle networks than in liver or adipose tissue (van Nas et al 2009; Wong et al 2014). Liver tissue is considered a highly sexually dimorphic tissue, particularly in oviparous species at a reproductive stage (Qiao et al 2016). Although the extent of differences may depend on the tissue of study, network comparisons between sexes can provide new insight into the regulatory underpinnings of sexual dimorphism and antagonism.…”
mentioning
confidence: 99%
“…According to the literature, liver has been found to be a key organ for absorption, bioaccumulation, energy metabolism, protein biosynthesis, xenobiotic detoxification, endocrine as well as immune responses in multiple toxicity studies _ (Qiao et al, 2016). Therefore, the specific reason behind the alterations found in this work in liver might be the effect of any of them or even the combination of a few ones.…”
Section: Ymentioning
confidence: 85%
“…But the information regarding the unidentified MC-transporting OATPs and their expression level on germ cells remains very limited. Due to various physiological differences between female and male fish (Qiao et al, 2016b), the toxic effects of MC on gonads of two genders of fish seem to be different. One previous study demonstrated that female zebrafish are more vulnerable than males to MC-LR exposure indicated by more cell apoptosis in ovary compared with testis (Qiao et al, 2013).…”
Section: Resultsmentioning
confidence: 99%